The accuracy of markerless motion capture combined with computer vision techniques for measuring running kinematics - Van Hooren, B.; Pecasse, N.; Meijer, K.; Essers, J. M. N. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Background Markerless motion capture based on low-cost 2-D video analysis in combination with computer vision techniques has the potential to provide accurate analysis of running technique in both a research and clinical setting. However, the accuracy of markerless motion capture for assessing running kinematics compared to a gold-standard approach remains largely unexplored.